Centering animals in Latin American history - Few, Martha 1964-; Tortorici, Zeb 1978- (Duke University Press, 2013)
Writing animal histories / Zeb Tortorici and Martha Few -- The year the people turned into cattle : the end of the world in New Spain, 1558 / León García Garagarza -- Killing locusts in colonial Guatemala / Martha Few -- "In the name of the father and the mother of all dogs" : canine baptisms, weddings, and funerals in Bourbon Mexico / Zeb Tortorici -- From natural history to popular remedy : animals and their medicinal applications among the Kallawaya in colonial Peru / Adam Warren -- Pest to vector : disease, public health, and the challenges of state-building in Yucatán, Mexico, 1833-1922 / Heather McCrea -- Notes on medicine, culture, and the history of imported monkeys in Puerto Rico / Neel Ahuja -- Animal labor and protection in Cuba : changes in relationships with animals in the nineteenth century / Reinaldo Funes Monzote -- On edge : fur seals and hunters along the Patagonian littoral, 1860-1930 / John Soluri -- Birds and scientists in Brazil : in search of protection, 1894-1938 / Regina Horta Duarte -- Trujillo, the goat : of beasts, men and politics in the Dominican Republic / Lauren Derby -- Conclusion: loving, being, and killing animals : an afterword on "centering animals" / Neil L. Whitehead